The Meaning Construction of Public Relations Marketing of Islamic Private Higher Education PR - Wiwitan, Tresna; Yulianita, Neni (Jurnal The Messenger, 2018)
The reality that occurs today is that Private Universities is still unable to compete with State Universities. Unisba and Unissula are Islamic Private Universities working hard to gain public trust through improving the academic quality of the lecturers and the students. Research issue that will be studied is the dimension of the meaning construction of PR Marketing in Unisba and Unissula. This research is qualitative research with case study approach. The theory used to examine and to analyze the results of the research is the Theory of Social Construction (Berger and Luckman). The results of research stated that the meaning construction of PR Marketing are: 1) the art of persuading the stakeholders in the framework of human relations, 2) the intention of worshipping because of Allah SWT (Lillahi Ta'ala) based on patience, honesty, and exemplary, 3) the motive to increase the number of prospective students and to build positive image, and 4) PR Marketing puts forward the values of Islam that contains the values of Islamic da'wah and syi'ar.